RESEARCH PAPER: DIAGNOSTIC ACCURACY OF MODIFIED ALVARADO SCORE IN THE DIAGNOSIS OF ACUTE APPENDICITIS KEEPING HISTOPATHOLOGY AS GOLD STANDARD (Journal of Medical & Health Sciences Review, 2025)
The purpose of this study was to assess the performance of the Modified Alvarado Score (MAS) for diagnosing acute appendicitis against histopathology as the reference standard. Acute appendicitis is one of the most frequent surgical emergencies due to the potential risk of complications including perforation, abscess formation, and sepsis. However, diagnosing it is not easy because its symptoms are vague, and this has given rise to systems such as the MAS. In this cross-sectional study carried out at Mardan Medical Complex in Mardan, Pakistan, 179 of consumers were administered the MAS and surgically treated for appendectomy for histopathological confirmation. The study showed that the MAS had a good sensitivity of 83.3% and moderate specificity of 72.2% in diagnosing acute appendicitis, a positive predictive value of 86.7 and a negative predictive value of 68.9 %. Subgroup analysis illustrated that the diagnostic accuracy of the MAS was higher in the 18–30 years age group and males and slightly lower in the older age and females. Moreover, using diagnostic accuracy as a measure, the outcome was significantly affected by SES: the middle-SES group had the highest performance. The findings of the study enhance the utilization of MAS as a simple and non-invasive approach to diagnosing appendicitis, particularly in resource-challenged areas where imaging is rare. However, the moderate